Self-care in individuals with chronic kidney disease on hemodialysis - Santana, Mariela Beatriz Andrade; Silva, Denise Maria Guerreiro Vieira da; Echevarría-Guanilo, Maria Elena; Lopes, Soraia Geraldo Rozza; Romanoski, Priscila Juceli; Böell, Julia Estela Willrich (My University, 2020)
ABSTRACT Objective: To understand how self-care is carried out by people with chronic kidney disease on hemodialysis. Method: A qualitative approach was used. Data was collected through semi-structured interviews in 12 individuals on hemodialysis in Chile between September and December 2018. Dorothea Orem's self-care theory was used for directed content analysis. Results: Three categories emerged: self-care requirements, self-care deficit, and education and information management for self-care. People were aware of the importance of carrying out their self-care. They also stated not to carry out the care actions rigorously enough showing some limitations. Finally, people's knowledge about their condition was usually acquired from the Internet and from their own experience rather than through consultations with a health team. Considerations: People are conscious about their role in their health in a flexible way. The health team should know how to recognize conditions interfering in people's self-care and help to overcome them.
Keywords: kidney dialysis; kidney insufficiency, chronic; chronic disease; self-care